Multivariate analysis in cytoplasmic male sterile lines of rice (Oryza sativa L.) - Ansari, A; Rasul, MG; Julfiqer, AW; Rahman, MM; Shasunnaher, M (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(2) December 2009 25-28